2012
DOI: 10.1055/s-0040-1703549
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of Foramen Magnum for Sex Determination in South Indian Population

Abstract: In this study the foramen magnum was analyzed for sex differences using standard osteometric techniques.We analyzed 100 (55 males and 45 females) skulls from the department of Anatomy, Yenepoya Medical College which were in good condition with a record of sex. The cranial base was visually assessed for foramen magnum shape. Morphometry (anteroposterior diameter (APD) & Transverse diameter (TD)) was determined and their differences by gender (p<0.05) were ascertained.Oval shape was the most common followed by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Conversely, multiple investigations in India[ 24 , 28 , 31 , 32 ] have shown a similar trend where, generally, men tend to have larger measurements in both length and width of the foramen magnum and condyles compared to women. Although variability in the data is observed, this persistent discrepancy between sexes is a notable finding.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Conversely, multiple investigations in India[ 24 , 28 , 31 , 32 ] have shown a similar trend where, generally, men tend to have larger measurements in both length and width of the foramen magnum and condyles compared to women. Although variability in the data is observed, this persistent discrepancy between sexes is a notable finding.…”
Section: Discussionmentioning
confidence: 88%
“…[ 7 ] For instance, analyses in Europe have highlighted variations between genders in foramen magnum measurements,[ 5 , 8 , 9 , 11 , 16 , 23 , 25 , 26 , 38 ] while in Asia, distinct differences between men and women in various cranial measurements have been observed. [ 14 , 18 , 24 , 28 , 31 , 32 , 34 ] These anatomical discrepancies can influence surgical techniques, emphasizing the relevance of an approach tailored to the region and/or geographical area to enhance the outcomes of craniotomies.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies conducted on different populations have concluded that males have larger foramen magnum lengths and widths than females which is compatible with the findings of the current study. [2,4,9,10,13,[15][16][17] A Brazilian study had also shown that width specifically is significantly larger in males. [18] A study on Eastern European individuals and another on the Indian population which involved the measurement of length, width, and area of foramen magnum concluded that all three parameters were significantly higher in males.…”
Section: Discussionmentioning
confidence: 99%